1996
DOI: 10.1021/jo961004i
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C(5)−C(5a) Exomethylene Group in Bicyclomycin:  Synthesis, Structure, and Biochemical and Biological Properties

Abstract: Thirty-two C(5)-C(5a) exomethylene-modified bicyclomycin derivatives were prepared to determine the effect of structural modification of this unit on bicyclomycin (1) function. The compounds were grouped into three categories: the C(5)-unsaturated bicyclomycins, the C(5a)-substituted C(5)-C(5a)-dihydrobicyclomycin derivatives, and the C(5)-modified norbicyclomycins. An efficient three-step procedure was developed to synthesize C(5a)-substituted C(5),C(5a)-dihydrobicyclomycins. Bicyclomycin was converted to bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 24 publications
6
42
0
Order By: Relevance
“…2 The use of analogues acting as irreversible inactivators has proven to be a useful approach for the identification of substrate-binding sites in enzymes (30). A recent structure-activity relationship study of Bcm (31)(32)(33) has identified 5a-(3-formylanilino)dihydrobicyclomycin (FD-Bcm) as a potential reductive amination probe that warranted further study (34). FD-Bcm has Rho inhibitory properties comparable with Bcm.…”
Section: Bicyclomycin (Bcm)mentioning
confidence: 99%
“…2 The use of analogues acting as irreversible inactivators has proven to be a useful approach for the identification of substrate-binding sites in enzymes (30). A recent structure-activity relationship study of Bcm (31)(32)(33) has identified 5a-(3-formylanilino)dihydrobicyclomycin (FD-Bcm) as a potential reductive amination probe that warranted further study (34). FD-Bcm has Rho inhibitory properties comparable with Bcm.…”
Section: Bicyclomycin (Bcm)mentioning
confidence: 99%
“…In the first, we determined the structureactivity relationship (SAR) for bicyclomycin inhibition of rho [119][120][121][122][123][124][125][126][127][128][129][130][131]. In the second, we identified key amino acid residues in rho necessary for rho binding [74].…”
Section: Preliminary Studies On the Identi-fication Of The Bicyclomycmentioning
confidence: 99%
“…More than 75 C(5)-C(5a) exomethylene-modified bicyclomycin derivatives were prepared [125][126][127][128][129][130][131]. The compounds can be grouped into three categories (Figure 9): C(5)-unsaturated bicyclomycins A [125,126], C(5a)-substituted C(5)-C(5a)-dihydrobicyclomycins B [125,[127][128][129][130], and C(5)-modified norbicyclomycin C [131].…”
Section: The C(5)-c(5a) Exomethylene Groupmentioning
confidence: 99%
See 2 more Smart Citations